Silane cross-linked polyethylene insulation material for heating cable and preparation method thereof

By optimizing the formulation and processing technology of silane crosslinked polyethylene insulating materials, the problems of unstable material performance and complex processing in heating cable applications are solved, and materials with high mechanical strength and flexibility are prepared, which enhances the market competitiveness of the products.

CN119752002APending Publication Date: 2025-04-04ZHEJIANG QINGQICHEN ELECTRIC HEATING CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411616030.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the application of silane crosslinked polyethylene insulating materials, there are problems such as complex processing technology and instable material performance in heating cables, and cannot fully meet the market's demand for high-performance heating cables.

Method used

By optimizing formulation design, improving processing technology and using high-efficiency catalysts, multiple polyolefin resins are selected in specific proportions, using temperature gradient control technology and efficient mixing section screw design, ensuring that the components are fully melted and mixed evenly at the appropriate temperature.

Benefits of technology

It realizes the high mechanical strength, good flexibility and bending performance of the material, and improves the stability of the processing process and the market competitiveness of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides a silane cross-linked polyethylene insulating material for heating cables and a preparation method thereof, wherein the insulating material is prepared by mixing the following raw materials in parts by weight: 70-100 parts of polyolefin resin; 1.5-2.5 parts of silane cross-linking agent; 0.3-0.6 parts of grafting initiator; 0.2-0.6 parts of first lubricant; 0.1-0.3 parts of first antioxidant; 1.0-2.5 parts of cross-linking catalyst; 0.2-0.5 parts of second lubricant; 0.1-0.3 parts of second antioxidant; 5-15 parts of ethylene-vinyl acetate copolymer; 0.5-2 parts of maleic anhydride grafted polyethylene; 0.1-0.3 parts of ultraviolet absorber; 0.1-0.3 parts of antistatic agent. The preparation method includes mixing, melt blending, extrusion granulation, cross-linking molding and cooling and shaping. The finished product of the present invention has better performance, more stable production and more competitive cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cables, and in particular to a silane cross-linked polyethylene insulating material for heating cables and a preparation method thereof. Background Art

[0002] Silane cross-linked polyethylene (XLPE) is a polymer material that forms a three-dimensional network structure by chemically cross-linking polyethylene molecular chains. Its main features include excellent electrical insulation, heat resistance, chemical corrosion resistance and mechanical strength. Compared with traditional thermoplastic polyethylene, silane cross-linked polyethylene can maintain a stable structure at high temperatures and is not easy to melt and deform. Therefore, it is widely used in wires, cables, pipelines and other fields.

[0003] In the field of heating cables, silane cross-linked polyethylene materials have become an ideal choice of insulation materials due to their excellent high temperature resistance and insulation properties. Heating cables are usually used in floor heating systems, snow melting systems and some industrial heating equipment in buildings. These application scenarios require cables to maintain stable performance for a long time in high temperature and humid environments and provide safe and reliable electrical insulation.

[0004] However, silane cross-linked polyethylene also faces some technical difficulties when applied to heating cables. First of all, how to ensure uniform cross-linking degree and sufficient mechanical strength during the production and processing of the material is an important challenge. Excessive cross-linking will cause the material to become brittle and affect the flexibility of the cable; insufficient cross-linking will lead to a decrease in the thermal stability and insulation performance of the material. Secondly, the silane cross-linking reaction needs to be carried out under specific humidity and temperature conditions. How to effectively control the cross-linking conditions in large-scale production is also a technical challenge. In addition, the selection of catalysts and formula design in the cross-linking process have a key influence on the final performance of the material. How to optimize these factors to meet the needs of different application scenarios is also the focus of current technical research.

[0005] In the prior art, the degree of crosslinking and mechanical properties of the material are controlled by adjusting the dosage of the silane crosslinking agent and the ratio of the grafting initiator; the temperature and humidity of the crosslinking curing are precisely controlled to ensure uniform crosslinking of the material. However, these methods still have some disadvantages in practical applications, such as high production costs, complex processing technology, and unstable material properties, which cannot fully meet the market demand for high-performance heating cables.

[0006] Therefore, there is an urgent need for a new technical solution that can effectively solve these problems in the application of silane cross-linked polyethylene insulation materials in heating cables and provide a material solution with better performance, more stable production and more competitive cost. Summary of the invention

[0007] According to the technical problems raised above, a silane cross-linked polyethylene insulation material for heating cables and a preparation method thereof are provided. The present invention mainly solves the problems of complex processing technology and unstable material performance of silane cross-linked polyethylene insulation materials in heating cable applications by optimizing formula design, improving processing technology and using high-efficiency catalysts.

[0008] The technical means adopted by the present invention are as follows:

[0009] A silane cross-linked polyethylene insulation material for a heating cable, the insulation material is made by mixing the following raw materials in parts by weight:

[0010] 70-100 parts of polyolefin resin; 1.5-2.5 parts of silane crosslinking agent; 0.3-0.6 parts of grafting initiator; 0.2-0.6 parts of first lubricant; 0.1-0.3 parts of first antioxidant; 1.0-2.5 parts of crosslinking catalyst; 0.2-0.5 parts of second lubricant; 0.1-0.3 parts of second antioxidant; 5-15 parts of ethylene-vinyl acetate copolymer; 0.5-2 parts of maleic anhydride grafted polyethylene; 0.1-0.3 parts of ultraviolet absorber; 0.1-0.3 parts of antistatic agent.

[0011] Furthermore, the polyolefin resin is composed of low-density polyethylene, linear low-density polyethylene, high-density polyethylene and polypropylene, and the feed mass ratio of the low-density polyethylene, the linear low-density polyethylene, the high-density polyethylene and the polypropylene is 2-10:1.5-6:0.7-4:1.

[0012] Specifically, the low-density polyethylene has good flexibility, impact resistance and transparency; compared with low-density polyethylene, the linear low-density polyethylene has higher strength and tear resistance while maintaining good flexibility; the high-density polyethylene has higher crystallinity and strength, and lower ductility; the polypropylene has a higher melting point, good chemical resistance and rigidity, and is suitable for working conditions requiring heat resistance.

[0013] In addition, the addition of ethylene-vinyl acetate copolymer improves the toughness and flexibility of the material, while maleic anhydride grafted polyethylene enhances the polarity of the material, making it more compatible with the silane crosslinker, further improving the processability of the material and the performance of the final product. By adding ultraviolet absorbers and antistatic agents, the weather resistance and protection of the material are enhanced, extending the service life of the cable in outdoor and harsh environments.

[0014] Furthermore, in parts by weight, the raw materials of the polyolefin resin include 25-45 parts of low-density polyethylene, 20-28 parts of linear low-density polyethylene, 8-19 parts of high-density polyethylene, and 4-14 parts of polypropylene.

[0015] Further, the silane crosslinking agent is selected from one or a combination of vinyl triethoxysilane, vinyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, vinyl triisopropoxysilane and methyl triethoxysilane. The silane crosslinking agent can react with water under subsequent humidity conditions to form a crosslinking network, and the amount of the silane crosslinking agent is slightly reduced to avoid excessive crosslinking, thereby maintaining the flexibility of the material while ensuring sufficient crosslinking.

[0016] Furthermore, the crosslinking catalyst is selected from one or a combination of dibutyltin dilaurate, diethyltin dilaurate, dibutyltin oxide, zinc diethyldithiocarbamate and dioctyltin dithiocarbamate, and its function is to promote the crosslinking reaction of silane groups in the presence of water.

[0017] Furthermore, the grafting initiator is one or a combination of dicumyl peroxide, 1,1-di-tert-butylperoxide-3,3,5-trimethylcyclohexane and dibenzoyl peroxide. By increasing the proportion of the grafting initiator, the grafting reaction is ensured to be fully carried out, thereby improving the uniform cross-linking degree of the material.

[0018] Furthermore, the first lubricant and the second lubricant are both selected from one or a combination of PE wax, EVA wax and PPA. The lubricant can improve the fluidity during mixing and extrusion, increase the amount of lubricant, improve the processing performance and uniformity of the material, and avoid uneven local cross-linking.

[0019] Furthermore, the first antioxidant is selected from one or a combination of antioxidant 1010, antioxidant 1076 and antioxidant 300; the second antioxidant is antioxidant 1024. The function of the antioxidant is to improve the thermal stability of the material and prevent thermal oxidation degradation of polyethylene during processing.

[0020] The present invention also provides a method for preparing the above-mentioned silane cross-linked polyethylene insulation material for heating cables, comprising the following steps:

[0021] S1. Raw material preparation and mixing: According to the preset number of weighed raw material components, polyolefin resin, silane crosslinking agent, grafting initiator, ethylene-vinyl acetate copolymer, and maleic anhydride grafted polyethylene are preliminarily mixed in a high-speed mixer at a speed of 1200-1500 rpm for 5-10 minutes at room temperature; lubricant, antioxidant, ultraviolet absorber, and antistatic agent are continuously added and mixed at the same speed for 3-5 minutes to ensure that all components are evenly distributed;

[0022] S2, melt blending: the mixed materials are put into a twin-screw extruder, and melt blended at a temperature range of 160-190°C, and the melting time is controlled at 5-8 minutes, and the specific time is adjusted according to the viscosity of the materials; the silane crosslinking agent undergoes a grafting reaction with the polyethylene matrix to form a pre-crosslinked polymer;

[0023] S3, extrusion granulation and drying: the melt blended material is extruded into strips at 180-200°C through an extruder head, and quickly cooled to 30-50°C through a water cooling system before pelletizing; the granulation process lasts about 10-15 minutes, and the cooling time is usually 1-2 minutes; the granulated material is placed in an oven at 70-90°C for 2-4 hours to remove residual moisture and prevent hydrolysis reaction in subsequent processing;

[0024] S4, cross-linking and molding: The dried granular material is processed into a cable insulation layer through an extrusion device at a temperature of 180-210°C. The extrusion process usually lasts 10-20 minutes, depending on the thickness of the product. The molded cable insulation layer is cross-linked in a hot water or steam environment at 80-100°C. The cross-linking time is usually 4-8 hours to ensure sufficient cross-linking.

[0025] S5. Cooling, shaping and packaging: After cross-linking is completed, the cable is cooled to room temperature in cooling water. The cooling time is usually 15-30 minutes. The cooled cable is inspected to ensure that the product size, mechanical strength and electrical performance meet the requirements, and then packaged and stored.

[0026] Furthermore, in step S2, the temperature zones of the twin-screw extruder are set to be progressive, namely, 150-160°C in the feeding zone; 170-180°C in the middle zone; and 180-200°C in the discharging zone.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] The present invention selects a variety of polyolefin resins and uses them in combination in a specific ratio, so that the material has good mechanical strength, heat resistance and flexibility at the same time. Among them, the high flexibility and processing performance of low-density polyethylene ensure the bendability and construction convenience of the insulation material at low temperatures; linear low-density polyethylene provides better impact resistance and environmental stress cracking resistance; high-density polyethylene improves the heat resistance and mechanical strength of the material; and polypropylene plays a key role in improving the chemical resistance and dimensional stability of the material. The synergistic effect of these polyolefins makes the prepared silane cross-linked polyethylene insulation material show excellent stability under different temperature and load conditions.

[0029] In the preparation method, the present invention significantly improves the uniformity and processing efficiency of the material by optimizing the melt blending and granulation process. The temperature gradient control technology is used to accurately divide the temperature in the melting process, thereby avoiding the problem of local overheating or underheating, and ensuring that each component is fully melted and evenly mixed at a suitable temperature. At the same time, the use of the high-efficiency mixing section screw design makes the shearing effect more ideal, the uniformity of the material is further improved, and the risk of possible uneven mixing and local defects is reduced.

[0030] In summary, the present invention solves the problems of poor uniformity, insufficient mechanical strength, high processing energy consumption, etc. in the prior art. Without changing the basic polyethylene resin, by adjusting the composition of each raw material and the raw material ratio, the material has excellent flexibility and bending performance while maintaining high mechanical strength, and is particularly suitable for use in complex construction environments. By improving the processing method, it is ensured that each component is fully melted at a suitable temperature, thereby improving the stability of the processing process and reducing the scrap rate.

[0031] The present invention provides a more efficient, economical and reliable solution for the preparation of silane cross-linked polyethylene insulation materials for heating cables, effectively improving the market competitiveness and application prospects of the products, especially in high-demand industrial and construction fields. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] The present invention provides a silane cross-linked polyethylene insulation material for a heating cable, which is composed of the following raw materials in parts by weight: 70 parts of polyolefin resin (30 parts of low-density polyethylene, 25 parts of linear low-density polyethylene, 10 parts of high-density polyethylene, and 5 parts of polypropylene), 2.0 parts of a silane cross-linking agent, 0.4 parts of a grafting initiator, 0.5 parts of a first lubricant, 0.2 parts of a first antioxidant, 2.0 parts of a cross-linking catalyst, 0.3 parts of a second lubricant, 0.2 parts of a second antioxidant, 10 parts of ethylene-vinyl acetate copolymer, 1.0 parts of maleic anhydride grafted polyethylene, 0.2 parts of an ultraviolet absorber, and 0.2 parts of an antistatic agent.

[0035] Prepare according to the following preparation method:

[0036] S1. Raw material preparation and mixing: According to the preset number of weighed raw material components, the polyolefin resin, silane crosslinking agent, grafting initiator, ethylene-vinyl acetate copolymer, maleic anhydride grafted polyethylene and other components are preliminarily mixed in a high-speed mixer at a speed of 1200 rpm at room temperature (20-25° C.) for 5 minutes; lubricant, antioxidant, ultraviolet absorber, antistatic agent are continuously added, and mixed at the same speed for 3 minutes to ensure that all components are evenly distributed;

[0037] S2, melt blending: the mixed materials are put into a twin-screw extruder, and the temperature zones of the extruder are set: 150-160°C in the feeding zone, 170-180°C in the middle zone, and 180-200°C in the discharging zone, and melt blending is performed in the following ways. The screw speed is set to 200rpm, and the melting time is controlled to be 6 minutes. The silane crosslinking agent undergoes a grafting reaction with the polyethylene matrix to form a pre-crosslinked polymer. Preferably, a vacuum exhaust system can be used to remove volatiles and gases during the melting process to ensure the purity of the material.

[0038] S3, extrusion granulation and drying: the melt blended material is extruded into strips at 180-200°C through an extruder head, and quickly cooled to 30-50°C through a water cooling system before pelletizing; the granulation process lasts about 10 minutes, and the cooling time is usually 1-2 minutes; the granulated material is placed in an oven at 70-90°C for 2 hours to remove residual moisture and prevent hydrolysis reaction in subsequent processing;

[0039] S4, cross-linking and molding: The dried granular material is processed into a cable insulation layer through an extrusion device at a temperature of 180-210°C. The extrusion process usually lasts 10-20 minutes, depending on the thickness of the product. The molded cable insulation layer is cross-linked in a hot water or steam environment at 80-100°C. The cross-linking time is usually 4-6 hours to ensure sufficient cross-linking.

[0040] S5. Cooling, shaping and packaging: After cross-linking is completed, the cable is cooled to room temperature (20-25°C) in cooling water. The cooling time is usually 15 minutes. The cooled cable is inspected to ensure that the product size, mechanical strength and electrical performance meet the requirements, and then packaged and stored.

[0041] Examples 2-4 and Comparative Examples 1-2

[0042] Based on Example 1, the difference lies in the ingredients and contents, as shown in the following table:

[0043]

[0044]

[0045] The following are the experimental conditions used for testing samples of materials prepared in Examples 1-4 and Comparative Examples 1-2:

[0046] 1. Tensile strength test (GB / T 1040.3-2006)

[0047] Instrument: electronic universal material testing machine; sample size: length 160mm×width 20mm×thickness 1mm; test environment: room temperature (20-25℃), relative humidity 60%; test speed: 50mm / min; test method: clamp the sample in the fixture of the test machine. Stretch the sample at the specified test speed until it breaks. Record the maximum tensile load and calculate the tensile strength (MPa).

[0048] 2. Elongation at break test (GB / T 1040.3-2006)

[0049] Instrument: electronic universal material testing machine; sample size and test environment are the same as above; test speed: 50mm / min; test method: measure the initial length of the sample. Stretch the sample until it breaks and record the breaking length.

[0050] The elongation at break (%) was calculated as follows: [(break length-initial length) / initial length]×100%.

[0051] 3. Gel content test

[0052] Instrument: solvent extraction device; Sample size: about 5g (cut into small pieces); Solvent: ethanol; Test environment: room temperature (20-25℃); Test method: Place the sample in the solvent and extract for 24 hours. Take out the sample, dry it to constant weight, and weigh the dry weight.

[0053] Gel content (%) = [(initial mass - dry weight) / initial mass] x 100%.

[0054] 4. Thermal ductility test

[0055] Instrument: Thermal ductility test device; Sample size: 50mm long × 50mm wide × 1mm thick; Test environment: room temperature (20-25℃) and high temperature environment; High temperature environment: 80-100℃; Test method: Keep the sample in a high temperature environment for a period of time (usually 1 hour). Measure the dimensional change of the sample at high temperature.

[0056] Calculation of hot ductility (%) = [(size after heat treatment - original size) / original size] x 100%.

[0057] It should be noted that: in all tests, the thickness of the specimens should be consistent to ensure the accuracy and comparability of the test results. During the test, the environmental conditions should be kept stable to reduce the impact of external factors on the results.

[0058] The test results are shown in the following table:

[0059] Performance Indicators Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Tensile strength(MPa) 18.5 19.0 17.8 18.2 15.0 14.5 Elongation at break (%) 600 610 590 605 450 460 Gel content (%) 75.2 76.5 74.8 75.9 50.3 49.7 Hot ductility (%) 70.5 69.8 71.2 70.1 80.2 81.0

[0060] From the above test results, we can see that:

[0061] Tensile strength: The tensile strengths of Examples 1-4 are all between 17.8 and 19.0 MPa, showing high mechanical strength. However, the tensile strengths of Comparative Examples 1 and 2 are lower, 15.0 MPa and 14.5 MPa, respectively, indicating that the adjustment of the proportion of the components in the formula has a negative impact on the mechanical properties of the material.

[0062] Elongation at break: The elongations at break of Examples 1-4 are all between 590% and 610%, showing good flexibility of the material. The elongations at break of Comparative Examples 1 and 2 are significantly lower, 450% and 460% respectively, showing insufficient toughness of the material.

[0063] Gel content: Gel content is an important indicator for measuring the degree of crosslinking. The gel contents of Examples 1-4 are all between 74.8% and 76.5%, indicating that the crosslinking reaction is sufficient. However, the gel contents of Comparative Examples 1 and 2 are lower, 50.3% and 49.7% respectively, indicating that the crosslinking reaction is insufficient, which may lead to a decrease in the heat resistance and mechanical properties of the material.

[0064] Thermal ductility: The thermal ductility of Examples 1-4 is between 69.8% and 71.2%, indicating that the material has good dimensional stability when heated. However, the thermal ductility of Comparative Examples 1 and 2 is higher, 80.2% and 81.0% respectively, indicating that the material is easily deformed at high temperature and has poor stability.

[0065] In summary, from the test results, the materials prepared in Examples 1-4 showed excellent performance in tensile strength, elongation at break, gel content and thermal ductility, proving the rationality and effectiveness of the formula and process of the present invention. In contrast, Comparative Examples 1 and 2 showed a decrease in all performance indicators, indicating that under these comparative conditions, the material performance was poor, further proving the importance of optimizing the formula of the present invention.

[0066] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the above embodiments, a person of ordinary skill in the art should understand that any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A silane cross-linked polyethylene insulation material for heating cables, characterized in that: The insulating material is made by mixing the following raw materials in parts by weight: 70-100 parts of polyolefin resin; 1.5-2.5 parts of silane crosslinking agent; 0.3-0.6 parts of grafting initiator; 0.2-0.6 parts of first lubricant; 0.1-0.3 parts of first antioxidant; 1.0-2.5 parts of crosslinking catalyst; 0.2-0.5 parts of second lubricant; 0.1-0.3 parts of second antioxidant; 5-15 parts of ethylene-vinyl acetate copolymer; 0.5-2 parts of maleic anhydride grafted polyethylene; 0.1-0.3 parts of ultraviolet absorber; 0.1-0.3 parts of antistatic agent.

2. The silane cross-linked polyethylene insulation material for heating cables according to claim 1, characterized in that: The polyolefin resin is composed of low-density polyethylene, linear low-density polyethylene, high-density polyethylene and polypropylene, and the feed mass ratio of the low-density polyethylene, the linear low-density polyethylene, the high-density polyethylene and the polypropylene is 2-10:1.5-6:0.7-4:

1.

3. The silane cross-linked polyethylene insulation material for heating cables according to claim 2, characterized in that: In parts by weight, the raw materials of the polyolefin resin include 25-45 parts of low-density polyethylene, 20-28 parts of linear low-density polyethylene, 8-19 parts of high-density polyethylene, and 4-14 parts of polypropylene.

4. The silane cross-linked polyethylene insulation material for heating cables according to claim 1, characterized in that: The silane crosslinking agent is selected from one or a combination of vinyl triethoxysilane, vinyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, vinyl triisopropoxysilane and methyl triethoxysilane.

5. The silane cross-linked polyethylene insulation material for heating cables according to claim 1, characterized in that: The cross-linking catalyst is selected from one or a combination of dibutyltin dilaurate, diethyltin dilaurate, dibutyltin oxide, zinc diethyldithiocarbamate and dioctyltin dithiocarbamate.

6. The silane cross-linked polyethylene insulation material for heating cables according to claim 1, characterized in that: The grafting initiator is one or a combination of dicumyl peroxide, 1,1-di-tert-butylperoxide-3,3,5-trimethylcyclohexane and dibenzoyl peroxide.

7. The silane cross-linked polyethylene insulation material for heating cables according to claim 1, characterized in that: The first lubricant and the second lubricant are both selected from one or a combination of PE wax, EVA wax and PPA.

8. The silane cross-linked polyethylene insulation material for heating cables according to claim 1, characterized in that: The first antioxidant is selected from one or a combination of antioxidant 1010, antioxidant 1076 and antioxidant 300; the second antioxidant is antioxidant 1024.

9. A method for preparing a silane cross-linked polyethylene insulation material for a heating cable according to any one of claims 1 to 8, characterized in that The steps include: S1. Raw material preparation and mixing: According to the preset number of weighed raw material components, polyolefin resin, silane crosslinking agent, grafting initiator, ethylene-vinyl acetate copolymer, and maleic anhydride grafted polyethylene are preliminarily mixed in a high-speed mixer at a speed of 1200-1500 rpm for 5-10 minutes at room temperature; lubricant, antioxidant, ultraviolet absorber, and antistatic agent are continuously added and mixed at the same speed for 3-5 minutes to ensure that all components are evenly distributed; S2, melt blending: the mixed materials are put into a twin-screw extruder, and melt blended at a temperature range of 160-190°C, and the melting time is controlled at 5-8 minutes, and the specific time is adjusted according to the viscosity of the materials; the silane crosslinking agent undergoes a grafting reaction with the polyethylene matrix to form a pre-crosslinked polymer; S3, extrusion granulation and drying: the melt blended material is extruded into strips at 180-200°C through an extruder head, and quickly cooled to 30-50°C through a water cooling system before pelletizing; the granulation process lasts about 10-15 minutes, and the cooling time is usually 1-2 minutes; the granulated material is placed in an oven at 70-90°C for 2-4 hours to remove residual moisture and prevent hydrolysis reaction in subsequent processing; S4, cross-linking and molding: The dried granular material is processed into a cable insulation layer through an extrusion device at a temperature of 180-210°C. The extrusion process usually lasts 10-20 minutes, depending on the thickness of the product. The molded cable insulation layer is cross-linked in a hot water or steam environment at 80-100°C. The cross-linking time is usually 4-8 hours to ensure sufficient cross-linking. S5. Cooling, shaping and packaging: After cross-linking is completed, the cable is cooled to room temperature in cooling water. The cooling time is usually 15-30 minutes. The cooled cable is inspected to ensure that the product size, mechanical strength and electrical performance meet the requirements, and then packaged and stored.

10. The preparation method according to claim 9, characterized in that: In step S2, the temperature zones of the twin-screw extruder are set to be progressive, that is, the feeding zone is 150-160°C; the middle zone is 170-180°C; and the discharging zone is 180-200°C.

Citation Information

Cited By

  • One-step granulation method for polyethylene sheath material of optical cable

    CN121064551A

  • A one-step granulation method for an optical cable polyethylene sheath material

    CN121064551B

  • Reversible cross-linked polyethylene, preparation method thereof and application of reversible cross-linked polyethylene in cable material

    CN121343263A

  • Weather-resistant silane crosslinked polyethylene insulated power cable production process

    CN121554902A